Educational technology for promoting parental self-efficacy in controlling childhood asthma - Kamila Ferreira Lima; Ana Jéssica Lopes Dias; Ana Karen de Sousa Alves; Francisco Mateus Rodrigues Furtuoso; Thais de Queiroz Serra; Victórya Suéllen Maciel Abreu; Lorena Pinheiro Barbosa (Universidade Federal do Ceará, 2022)
Objective: to verify the self-efficacy of parents and caregivers in controlling childhood asthma before and after an educational intervention and to associate the scores with sociodemographic factors. Methods: quasi-experimental study, with 65 parents and caregivers of children with asthma. The Self-Efficacy and Their Child's Level of Asthma Control scale - Brazilian version - was used before and 30 days after the intervention with the reading of the booklet "Are you able to control your child's asthma - let's learn together?" For the analysis, McNemar's Chi-square and Wilcoxon statistical tests were used. Results: after 30 days,the effect of the intervention demonstrated statistical significance between high self-efficacy scores and the following variables: marital status (Odds Ratio:2.6;p≤0.001), family income (Odds Ratio:3.4;p≤0.001) and Bolsa Família Program benefit (Odds Ratio:2.9;p≤0.001). Conclusion: the educational booklet was shown to be effective in increasing the self-efficacy of parents and caregivers in the control and management of childhood asthma.